2022
DOI: 10.1101/2022.03.19.22272444
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Educational attainment, structural brain reserve, and Alzheimer’s disease: a Mendelian randomization analysis

Abstract: Higher educational attainment is observationally associated with lower risk of Alzheimer’s disease. However, the biological mechanisms underpinning this association remain unclear. The protective effect of education on Alzheimer’s disease may be mediated via increased brain reserve. We used two-sample Mendelian randomization to explore putative causal relationships between educational attainment, structural brain reserve as proxied by MRI phenotypes, and Alzheimer’s disease.Summary statistics were obtained fro… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 100 publications
(184 reference statements)
0
2
0
Order By: Relevance
“…We identified 75 SNPs that are strongly related to the neuroticism sum score (SUM) (F statistics: average 41.41, range 29.81-138.44). Similarly, representative SNPs were obtained for the 13 subclusters of neuroticism using the same method (24 SNPs for often feel "fed-up" [FED-UP], 25 ). They were all then included in the MR, which showed that the SUM is a cause of the onset of MD (OR = 1.682, 95% CI: 1.072-2.638, P = 0.024).…”
Section: The Causal Relationship Between Neuroticism and MDmentioning
confidence: 99%
See 1 more Smart Citation
“…We identified 75 SNPs that are strongly related to the neuroticism sum score (SUM) (F statistics: average 41.41, range 29.81-138.44). Similarly, representative SNPs were obtained for the 13 subclusters of neuroticism using the same method (24 SNPs for often feel "fed-up" [FED-UP], 25 ). They were all then included in the MR, which showed that the SUM is a cause of the onset of MD (OR = 1.682, 95% CI: 1.072-2.638, P = 0.024).…”
Section: The Causal Relationship Between Neuroticism and MDmentioning
confidence: 99%
“…The IVW method assumes that all included SNPs meet the IVs assumptions; the weighted median method assumes that only 50% of the included SNPs meet the IV assumption 24 ; and MR-Egger assumes that IVs will affect the outcome through confounding factors in addition to their effect on the exposure, which will result in weaker statistical power. 20 As IVW is currently the most widely accepted method used to determine causation relationships between exposure and outcome, 25,26 we also used IVW as our primary analytical method. For each method, we calculated the odds ratios (OR), 95% confidence intervals (CI), and P values.…”
Section: Two-sample Mrmentioning
confidence: 99%